Biosorption Of Chromium From Tannery Effluent Using Biomass Of Sargassum Wightii (Greville) - S.ABIRAMI,; S.SRISUDHA,; P.GUNASEKARAN, (International Journal of Pharma and Bio Sciences, 2012)
The release of chromium into water bodies is one of the major concerns of tannery industries. The present work deals with the determination of Chromium removal capacity of powdered biomass of Sargassum wightii (Greville) in synthetically prepared as well as real tannery effluent. The maximum adsorption was obtained after 12 hours of exposure at pH-4, in 8g/L biomass concentration of the seaweed biomass. The percentage of chromium removal increased with an increase in biomass concentration and contact time. At the same time, it was inversely proportional to initial metal concentration. Metal uptake capacity was found to increase on increasing initial metal concentration and it gets decreased with increase in biomass concentration. The maximum removal of 85.3±0.05% was observed in 50 mg/L of initial chromium concentration, using Sargassum wightii pretreated with 0.4 N sulphuric acid. Langmuir and Freundlich isotherms were used to derive equilibrium data.